ANALYSIS OF DYNAMICS PARAMETERS FOR THE STEEL CORD RUBBER CONVEYOR BELT - CHEN HongYue; ZHANG Kun; LI EnDong (Jixie qiangdu)
The determination of the dynamics parameters for the steel cord rubber conveyor belt is the key problem to research the dynamic characteristics and the operation energy consumption of the belt conveyor.Firstly,the transition state and the stable state for the dynamics parameters are defined according to the relaxation and the time-variant characteristics of the rubber conveyor belt.Secondly,the stress analytic solution of the conveyor belt under the dynamic strain is derived by taking the standard solid model as the viscoelastic constitutive model,the transition state and the stable state are analyzed according to the attenuation term in the analytic solution,and the general identification model and the simplified identification model for the standard solid model parameters of the conveyor belt are established.Finally,the dynamic strain loading experiment using st1600 steel cord rubber conveyor belt is performed,and the Matlab cftool tool box is employed to identify the experiment result.The result shows that under the experimental parameters,the difference between the general model identifying result and the simplified model identifying result decreases with the increase of loading cycling times,and the general model identifying result and the simplified model identifying result are the same and maintain stable when the loading cycling times is greater than 67.The loading cycling times or the loading cycling time that the general model identifying result and the simplified model identifying result are the same first can be taken as the criterion to distinguish the transition state and the stable state for the dynamics parameters of the conveyor belt.